Eligibility for free primary care and avoidable hospitalisations in Ireland - Anne Nolan (The Economic and Social Research Institute (ESRI), 2009)
Using hospital discharge data covering the period 1999-2004, the purpose of this paper is to examine the determinants of avoidable hospitalisations in Ireland, with a particular focus on the role of eligibility for free primary health care. Avoidable hospitalisations are those that are potentially avoidable with timely and effective access to primary care services and/or that can be treated more appropriately in a primary care setting, and are often used as an indicator of access to primary care. The issue is particularly relevant for Ireland, where access to free primary care is restricted to those on low incomes (with approximately 30 per cent of the population currently eligible). The results indicate that eligibility for free GP services, as well as GP availability, is significant in explaining the probability of being in hospital with an avoidable condition.
Keywords: 330; avoidable hospitalisation; primary care; eligibility; Ireland; Gesundheitsversorgung; Krankenhaus; Irland